Guide to Computer Network Security - Kizza, Joseph Migga (Computer Communications and Networks, 2009)
Contemporary societies have increasing dependence on computers and computer networks, and the increasing popularity of mobile computing, have given rise to numerous computer security problems. Yet despite a high proliferation of expert remedies, a viable and comprehensive solution to these security issues remains elusive, and society continues to suffer at the hands of cyber criminals, vandals and hackers. This authoritative Guide to Computer Network Security explores computer network infrastructures and protocol design security flaws, and discusses current security solutions and best practices in both fixed and mobile computer networks. The book broadly surveys thought-provoking security issues, discussing and raising questions about the impact of new technologies and protocols (with particular emphasis on the rapid growth and skyrocketing interests and use in mobile technologies). It further explores the security threats and vulnerabilities in the current network infrastructure and protocols, and outlines current security efforts. The text assumes a modest familiarity with basic computer programming and networking. Features: • Covers the very core of network security, and includes chapters about the very latest in 'handling disasters' and 'security in mobile network systems' • Presents an in-depth discussion of standardization, again informing the reader on current trends on the topic • Raises awareness of the security problems in cyberspace, and more particularly, computer network security • Discusses computer network infrastructure and protocol design flaws and vulnerabilities • Explores the role of legislation and law enforcement in maintaining computer and computer network security • Proposes efficient and widely acceptable solutions and best practices to security problems, and encourages readers to investigate other possible solutions • Alerts the reader to the daunting security problems in increasingly popular mobile network systems • Includes two types of end-of-chapter exercises: quickly workable questions, as well as more thought-provoking advanced exercises • Devotes one complete chapter to lab exercises: weekly, semester assignments and hard open-research projects • Endeavours to use open source software tools throughout • Provides support materials for lecturers and students such as PowerPoint slides, syllabus suggestions, solutions, instructor manual and student laboratory materials This text/reference is an invaluable instructional and research tool for undergraduates in computer and information security. It is also a rich resource for practitioners, and professionals looking to gain an understanding of computer network infrastructure and information network security. Dr Joseph Migga Kizza has also written Computer Network Security and Ethical and Social Issues in the Information Age. Key Topics: Network Vulnerabilities Hostile Scripts Security Assessment Authentication Cryptography Computer and Network Forensics Network Security Protocols Security in Wireless and Sensor Networks.